A Qualitative and Quantitative Study of Social Media Communicators: An Extension of Role Theory to Digital Media Workers. Issue 3 (2nd July 2016) - Carpenter, Serena; Lertpratchya, Alisa P.
Abstract : The life of knowledge workers in the information age is enwrapped in both uncertainty and opportunity. Organizations have faced ill-defined times by placing their confidence in the ability of digitally literate workers. We explored how social media communicators navigate the role stressors of this recently developed organizational position. The qualitative results revealed communicators struggled with and managed role ambiguity by relying on outside social media experts and Web analytics. A separate international quantitative survey of social communicators showed organizational leadership and social media self-development activities diminished levels of perceived ambiguity. The implications of this research suggest that organizational leaders possess minimal authority and influence in defining the role of knowledge workers.